Meta-Analysis: Breastfeeding and Its Correlation with Stunting - Azizah, Alfi Makrifatul; Dewi, Yulia Lanti Retno; Murti, Bhisma (Journal of Maternal and Child Health, 2022)
Background: Stunting is a problem of chronic malnutrition in the first 100 days of life, which can be prevented by breastfeeding in children. This study aims to analyze the relationship between breastfeeding and the incidence of stunting based on the results of a number of similar primary studies previously. Subjects and Method: This research was conducted using a meta-analysis study with PICO as follows: P= Children under five, I= Breastfeeding, C= Not Breastfeeding, O= Stunting. Article searches were conducted using electronic databases, namely PubMed, Goegle Scholar and Science Direct. Article searches were conducted using the keyword and Mesh methods as follows “Breastfeeding” AND “Stunting” AND “Children” “Breastfeeding and Malnutrition” OR “Breastfeeding Benefits”. sectional, the articles were analyzed using the Review Manager 5.3 application. Results: There were 8 articles from the continents of Africa, Asia and South America which included Ethiopia, Rwanda, Tanzania, Zambia, Pakistan, Indonesia, and Ecuador from 2001-2022 which were analyzed using PRISMA flow diagrams. Research studies show that children who are breastfed have a risk of experiencing stunting as much as 0.62 times compared to those who are not breastfed (aOR= 0.62; CI 95%= 0.41 to 0.94; p= 0.020). Conclusion: Breastfeeding can reduce the risk of children experiencing stunting.